Melting and heat generating influences on radiative flow of two-phase magneto-Williamson nanofluid via stretchable surface with slippage velocity and activation energy - Ullah, Imran; Jamshed, Wasim; Katbar, Nek Muhammad; Eid, Mohamed R.; Duraihem, Faisal Z.; Mohamed Isa, Siti Suzilliana Putri; Ibrahim, Rabha W.; AlDerea, Afrah M. (Taylor and Francis, 2024)
Melting heat and solutal transference in a magnetohydrodynamic flowing of Williamson nanofluid have been described, with the mathematical model guided by Arrhenius activation energy, chemically reactive species, and convective boundary restrictions. By implementing suitable similarity conversions, the regulating equations of partial differential equations (PDEs) (formed by continuity, impetus, energy, and concentricity components) are condensed to an arrangement of ordinary differential equations (ODEs). These commonalities are in nonlinear form, which includes the fluid’s velocity, heat, and concentration changes. Finally, the standard Keller box approach is used to solve this ODEs system computationally (KBM). Under the influence of regulating parameters, the computational results are tallied and displayed in suitable diagrams. The friction force factor, local Nusselt, and Sherwood values are tabulated. Furthermore, the velocity, energy, and concentration contours are plotted versus fluid thickness. The attributes of Williamson nanofluid flowing, melting heat transfer, and mass transference are debated in depth toward the end of this study. Among the most important outcomes that have been reached is that the rate of heat and solutal transport heightened between 52.5 and 55.2% by detraction of the magnetic field, Weissenberg number, and Brownian motion. We also found that there is an inverse relationship between the mass transmission and heat generating factor. © 2024 Taylor & Francis Group, LLC.